Socio-Cultural Determinants of Treatment Seeking Behavior among Tuberculosis Patients: A Systematic Review of a Qualitative Study - Imelda Sussanti Nailius; Dien Anshari (Humanistic Network for Science and Technology (HNST), 2022)
The treatment-seeking behavior of tuberculosis patients is an important component of tuberculosis control interventions. The author undertakes a systematic review by identifying, evaluating, and interpreting the findings of similar studies to determine socio-cultural factors affecting tuberculosis patients' treatment seeking behavior. This study employs meta-synthesis of qualitative method. The researcher search articles using keywords in the databases of Proquest, Ebsco, ScienceDirect, and Springerlink yielded results (n = 111,665). Furthermore, the screening, feasibility, and selection processes were carried out in the population of tuberculosis patients based on inclusion criteria such as complete scientific articles with qualitative research designs, including socio-cultural aspects influencing tuberculosis treatment seeking behavior which published in 2016 to 2021. As a result, there are 9 research publications which eligible for systematic review and meet the criteria. Socio-cultural factors of treatment seeking behavior of tuberculosis patients include factors of knowledge, awareness, belief, economic ability, facilities access and health facilities infrastructure, communication and family support, perceptions related to poverty, social and cultural stigma of seeking alternative medicine. Socio-cultural factors can be investigated and used as inputs in subsequent qualitative and quantitative research tailored to the characteristics and socio-cultural patterns found in Indonesia's tuberculosis patient population. Keywords: socio-cultural factors; health seeking behavior; tuberculosis